Impact of Women's Economic Activities in The Republic of Congo from 1990 to 2019 (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Since the XXth century, and especially after the Second World War, particular attention was given to the status of women who for many years was overs had owed. These different events led policy makers at the international level as well as in different countries of the world to make courageous decisions globally in favor of women globally. These decisions have enabled women to take flight both by integrating socially themselves and by taking beneficial actions that could contribute to the economic and social development of their respective countries. On the economic level in particular, Congolese women exercise many activities related to their own initiative or to collective action, these different activities contribute to the economic development of the Republic of Congo. In the economic field, the man alone cannot ensure the development of the country, the Congolese woman also contributes to this development.